PENGUATAN LITERASI KANA (HIRAGANA DAN KATAKANA) SEBAGAI DASAR KOMPETENSI BAHASA JEPANG BAGI CALON TENAGA KERJA MIGRAN DI KABUPATEN GOWA - Imelda; Kasmawati; Khairil Anwar; Nurfitri; Hadi Hidayat (Lafadz Jaya Publisher, 2026)
The community service program “Strengthening Kana Literacy (Hiragana and Katakana) as the Foundation of Japanese Language Competence for Prospective Migrant Workers in Gowa Regency” was implemented to improve the basic Japanese language competence of prospective migrant workers before they take the JLPT N4 or JFT-Basic A2 exams. This initiative aims to address the low level of kana literacy, which is a major obstacle to learning Japanese for migrant workers. The program utilized a 30-day intensive training program comprising 120 hours of instruction, employing a drilling-mnemonic-contextual approach, and utilizing character cards and digital applications for 50 participants. Evaluation results showed a significant improvement in kana literacy skills, with the average score rising from 30% on the pre-test to 82% on the post-test (an increase of 52.1%), including a 52.1% improvement in hiragana reading and an 80% improvement in katakana reading, both meeting the criteria for effectiveness. Participants were able to write 92 kana characters without errors, memorize 20 work-related vocabulary words per day, and engage in simple conversations in a workplace context. This program enhances job readiness in Japan through the SSW scheme and supports the national target of placing 100,000 migrant workers in Japan. Program recommendations include the development of N4-level job vocabulary and grammar modules, as well as ongoing collaboration between local governments, vocational training centers (LPK), and industry.